2017
DOI: 10.1186/s13054-017-1727-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting impaired myocardial relaxation in sepsis with a novel tissue Doppler parameter (septal e′/s′)

Abstract: BackgroundLeft ventricular diastolic dysfunction is associated with mortality outcomes in severe sepsis and septic shock. There are ongoing issues with diagnosing diastolic dysfunction in this cohort, partly owing to the poor applicability of traditional parameters in the hyperdynamic circulation. In this feasibility study, we sought to assess the utility of a novel parameter (septal e′/s′) to identify diastolic dysfunction in patients with severe sepsis and septic shock who had normal systolic function agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The peak early diastolic mitral annular velocities (e') were recorded at the septal site of the mitral annulus. The septal site was considered to have less translational movement and less Doppler beam angle error [16,17]. The e' was assessed as a feature of LV diastolic function [18].…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…The peak early diastolic mitral annular velocities (e') were recorded at the septal site of the mitral annulus. The septal site was considered to have less translational movement and less Doppler beam angle error [16,17]. The e' was assessed as a feature of LV diastolic function [18].…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…Prior studies have shown a linear relationship between systolic contraction and early diastolic recoil in healthy adults and have found heterogeneous relationships in disease states, such as heart failure, dilated cardiomyopathy, and sepsis (Clancy et al, 2017 ; Friedberg et al, 1985 ; Koh et al, 2010 ). Friedberg et al found a linear relationship between e’ and s’ in children and the s’/e’ ratio was altered in children with dilated cardiomyopathy while Koh et al found s’ and e’ remained associated in children with LV non‐compaction (Friedberg et al, 1985 ; Koh et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue Doppler imaging (TDI) was chosen to define LV longitudinal motion for several reasons. First, TDI permitted simultaneous measurement of the peak velocities and excursion distances of the mitral annulus for comparison (Clancy et al, 2017 ; Friedberg et al, 1985 ; Koh et al, 2010 ; Popovic et al, 2011 ). Second, TDI VTI is a previously validated measure of annular excursion (Hayashi et al, 2006 ; Manouras et al, 2009 ; Peverill, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, speckle tracking echocardiography is not available in most Polish intensive care units, so we try to apply tissue Doppler in many clinical scenarios. A very interesting application of tissue Doppler was proposed by Clancy et al [26]. They proposed a novel parameter (septal e'/s') to identify diastolic dysfunction in patients with severe sepsis and septic shock who had normal systolic function.…”
Section: Discussionmentioning
confidence: 99%